Keterampilan Menyimak sebagai Kunci Efektivitas Komunikasi dalam Pembelajaran Bahasa Indonesia di Sekolah Dasar - Pratiwi, Ni Made Wisudarini; Suarmayanti, Kadek Idha; I Wayan Widyastama; Ni Putu Sepnita Lestari Yanti; Ida Bagus Putrayasa (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Ibn Khaldun Bogor, 2025)
Listening skills are an important component in effective communication, especially in learning Indonesian at the elementary level. Unfortunately, this skill is still often neglected in learning practices, with a more dominant focus on reading and writing skills. This article aims to conceptually examine the importance of listening as a language skill, as well as to describe the accompanying micro skills, learning objectives, relevant learning activities, and effective strategies and evaluations in improving students' listening skills. This article is compiled using a qualitative descriptive approach based on literature reviews. The results of the study indicate that listening learning that is designed contextually, interactively, and varied can improve understanding of oral messages and form constructive communication in the classroom. Thus, listening must be positioned as an integral part of the comprehensive language learning process, and needs to be accompanied by in-depth evaluation to ensure the achievement of student competencies on an ongoing basis.